Edukasi dan Senam Hipertensi pada Lansia di Wilayah Kerja Puskesmas Berbah, Yogyakarta: Education and Hypertension Exercise for the Elderly in the Working Area of Berbah Health Center, Yogyakarta - Riyadi, Sujono; Warseno , Agus; Supatmi; Marmi (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
Hypertension is a chronic medical condition that requires continuous management to prevent life-threatening complications, especially in the elderly population. This article discusses a community service program involving education and hypertension exercise in the working area of the Berbah Health Center, Yogyakarta. The program addresses key issues such as low community awareness about blood pressure control and limited access to healthcare facilities. The methods used include three stages: preparation, implementation, and evaluation. The preparation stage involved assessing the needs of the elderly, coordinating with the health center, and preparing educational materials and logistics. The implementation stage comprised interactive health education sessions and hypertension exercise led by professional instructors. Finally, the evaluation stage involved pre- and post-tests to measure knowledge improvement and blood pressure reduction. The program targeted 60 elderly individuals, with 12 participants actively engaging in the activities. The results demonstrated that 75% of participants experienced significant improvement in their understanding of hypertension and a measurable reduction in blood pressure, highlighting the effectiveness of combining education and physical activity in community-based health programs.